Sentidos atribuídos por futuros professores de matemática ao processo de formação no programa de residência pedagógica - Altomare, Zilda de Carvalho Marani (2022)
This is qualitative research with the purpose of discussing the training of Mathematics undergraduate students who had the opportunity to experience school practice during their initial training in the Pedagogical Residency Program (PR). The aim was to answer the following question: What meanings are produced by future Mathematics teachers to the process of teacher training when they participate in the Pedagogical Residency program? The objectives to be reached are: 1. to identify evidence of remarkable experiences in the formation; 2. to identify, in the narrative of the future teachers, the practices developed during the program that were remarkable; 3. to understand the process of professional development of the preceptor. To this end, the study has as research subjects nine undergraduates from the Mathematics Undergraduate course at the Federal University of Lavras - MG, participants of the Pedagogical Residency Project. The production of data was constituted from the field diary and from the narratives produced in the narrative interviews and in the discussion/reflection group. By narrating their stories, the Residents reflected on their experiences and showed the meanings that they attributed to their experiences at that moment. Meanings, produced from other meanings. The results of the analysis of the Residents' accounts point to the importance of programs that aim to provide undergraduates with contact with the classroom during their initial training, such as the Pedagogical Residency. According to the Residents, the formative practices, such as theoretical studies, the search for the most adequate teaching and learning methodology to reach the set objectives, the writing of class narratives, shared teaching, and the sharing of narratives, were fundamental in their training.